Valence fluctuations of europium in the boride Eu4Pd29+xB8. (19th February 2016) - Gumeniuk, Roman; Schnelle, Walter; Ahmida, Mahmoud A; Abd-Elmeguid, Mohsen M; Kvashnina, Kristina O; Tsirlin, Alexander A; Leithe-Jasper, Andreas; Geibel, Christoph
Abstract: We synthesized a high-quality sample of the boride Eu4 Pd29+ x B8 ( x   =  0.76) and studied its structural and physical properties. Its tetragonal structure was solved by direct methods and confirmed to belong to the Eu4 Pd29 B8 type. All studied physical properties indicate a valence fluctuating Eu state, with a valence decreasing continuously from about 2.9 at 5 K to 2.7 at 300 K. Maxima in the T dependence of the susceptibility and thermopower at around 135 K and 120 K, respectively, indicate a valence fluctuation energy scale on the order of 300 K. Analysis of the magnetic susceptibility evidences some inconsistencies when using the ionic interconfigurational fluctuation (ICF) model, thus suggesting a stronger relevance of hybridization between 4 f and valence electrons compared to standard valence-fluctuating Eu systems.